2011
DOI: 10.1186/1471-2369-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic consequences of changing potassium concentrations in haemodialysis fluids

Abstract: BackgroundA rapid decrease of serum potassium concentrations during haemodialysis produces a significant increase in blood pressure parameters at the end of the session, even if effects on intra-dialysis pressure are not seen. Paradoxically, in animal models potassium is a vasodilator and decreases myocardial contractility. The purpose of this trial is to study the precise haemodynamic consequences induced by acute changes in potassium concentration during haemodialysis.MethodsIn 24 patients, 288 dialysis sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…This may be especially problematic in cases where the DK administered during the treatment directly preceding an arrhythmic event differed from the standing prescription. Similarly, DK profiling, the varying of DK during a single HD session, 31,32,34 was not captured in the DOPPS and thus we cannot calculate its prevalence nor speculate on its effect on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be especially problematic in cases where the DK administered during the treatment directly preceding an arrhythmic event differed from the standing prescription. Similarly, DK profiling, the varying of DK during a single HD session, 31,32,34 was not captured in the DOPPS and thus we cannot calculate its prevalence nor speculate on its effect on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One can argue that Finometer is not a well‐validated method to access hemodynamic changes during dialysis. However, it should be pointed out that this device has already been tested against intra‐arterial BP in hypertensive patients and has also been cited in several publications on dialysis patients with consistent results . In fact, one study found that the absolute cardiac output values reported by Finometer were unreliable .…”
Section: Discussionmentioning
confidence: 91%
“…Whatever the risk of death of using a low dialysate potassium, it does have cardiac and hemodynamic consequences which place the patient risk. In a blinded crossover study of 24 patients with variations in dialysate potassium, the lower potassium lead to a lower mean blood pressure and a decrease in peripheral resistance . In another crossover study of 42 people on dialysis a larger gradient between plasma and dialysate potassium early in dialysis was associated with an increased frequency of premature ventricular contractions, and their coupling …”
Section: Mortality (Per 10 000 Person Years) Associated With a High Omentioning
confidence: 99%